Effect of Simple Reaction Speed Training on Executive Function of the Elderly with Mild Cognitive Impairment - Hong ZHANG; Xiaofei WEI; Congyong LIU; Kaili QIAN; Chun LI; Rang LI; Yuan JIANG (康复学报)
Objective:To observe the effect of simple reaction speed training on executive function of the elderly with mild cognitive impairment (MCI).Methods:A total of 64 elderly with MCI were selected by convenient sampling method from Xindu district of Chengdu City from January 2016 to June 2018, which were randomly divided into the control group and the observation group, with 32 cases in each group. The control group only received MCI health education, once every two weeks, continuous intervention for three months. The observation group received simple reaction speed training on the basis of the control group.④Decomposition training: walking on flat ground decomposition training, going up and down stairs decomposition training, crossing obstacles decomposition training, 10 times a group, two groups a day.④Complete training: walking on flat ground complete training, going up and down stairs complete training, 10 times a group, one group a day; crossing obstacles complete training, five times a group, one group a day.④Change training: according to the instruction of command or signal light, the subject makes corresponding actions or actions contrary to the instruction, three times a group, one group a day.④Sense of movement training: single training of walking on flat ground training, going up and down stairs training and crossing obstacles training, three times a group, one group a day. Each training time was 30-40 min, once a day, five times a week, continuous intervention for three months. The behavior rating inventory of executive function-adult version[BRIEF-A, including behavior regulation index (BRI), metacognitive index (MI)], behavioral assessment of dysexecutive syndrome[BADS, including rule switching card test (RSCT), action plan test (APT), key seek test (KST), time judgment test (TJT), zoo map test (ZMT), modified six-element test (MSET) ]and trail making test (TMT, including TMT-A and TMT-B) were used to evaluate the executive function of patients with MCI before and after intervention, respectively. Moreover, the serum brain-derived neurotrophic factor in the blood before and after intervention was detected by using enzyme linked immunosorbent assay (ELISA), respectively.Results:Compared with before intervention, the scores of conversion, working memory, planning, task monitoring, MI, total standard scores, TMT-B and interference in the observation group after intervention for three months were significantly lower, KST, TJT, ZMT, total standard scores and level of serum BDNF of the observation group after intervention were significantly higher (P< 0.05); compared with the control group, the scores of conversion, task initiation, working memory, planning, BRI, MI, total standard scores, TMT-B and interferences of the observation group were significantly lower, and RSCT, KST, TJT, ZMT, total standard scores and level of serum brain-derived neurotrophic factor (BDNF) of the observation group were significantly high (P< 0.05).Conclusion:Simple reaction speed training can improve the executive function, brain nerve function, and effectively delay cognitive decline of elderly with MCI.